METODE KONSELING INDIVIDU DALAM MENGATASI KONFLIK PERTEMANAN ANTAR SISWA KELAS X MAN 2 SLEMAN (STUDI KASUS TERHADAP 2 SISWA) - Zakka Nurlatifah Khasanah (UIN Sunan Kalijaga Yogyakarta, 2018)
This study aims to determine the methods used by counseling teachers in dealing with student friendship conflicts. This research is descriptive qualitative with case study research. The data source of this research is counselor guidance and counseling is Yuni Heru Kusumawardani, guidance and counseling teacher Mr. Ruba'i and two students of class X MAN 2 Sleman. Data collection was done by interview method, documentation and observation. The results showed that the method of individual counseling to cope with conflicts friendship between students of class X MAN 2 Sleman is a directive method and eclectic method. The directive method is given to the PPA at the first meeting until the third, whereas APE is given at the first and second meeting, the directive method is used when the counseling teacher searches the data or digs the information about the problem that is being experienced by the student, in this directive method the counseling guidance teacher can make a diagnosis related to the problems experienced by the students at that time. Furthermore, the eclective method is given to the PPA at the fourth to sixth meetings, whereas the APE is given at the third and fourth meetings, the eclective method is used when the counseling teacher checks by hearing what statements and decisions or commitments the student will make on the method This counseling teacher's eclectic counseling can conduct joint evaluations with the students.Keywords: Individual Counseling, Conflict Friendship